Analisi Faktor Terhadap Penyimpangan Keuangan Negara Tahun 1999/2000 (Dengan Pendekatan Component Analysis - Manggala, Budi (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2000)
From the audit report for the fiscal year 1999/2000, it has been fount out some disrepancies in the goverment finance for as Rp 165, 850 billion bye the Suprame Audit Board (SAB)